Direct methane conversion with oxygen and CO over hydrophobic dB-ZSM-5 supported Rh single-atom catalyst - Honglin Wang (Elsevier, 2022)
Isolated Rh atoms are supported on hydrophobic dB-ZSM-5. Single-atom Rh on dB-ZSM-5 is characterized with Ac-HAADF/STEM and CO adsorption FTIR. Direct conversion of methane to oxygenates is carried out in an autoclave in water charged with CH4, O2 and CO at 150 °C. Hydrophobic Rh-dB-ZSM-5 is compared with hydrophilic Rh-ZSM-5 (Si/Al = 15) for its catalytic performance. Rh-dB-ZSM-5 catalyst exhibits higher CH3OH selectivity and lower CH3COOH and CO2 selectivity. The catalytic activity of Rh-dB-ZSM-5 is much higher than the activity of Rh-ZSM-5 when the reaction is carried out under low pressure.